Effect of Body Mass Index on Venous Sinus Pressures in Idiopathic Intracranial Hypertension Patients Before and After Endovascular Stenting. Issue 4 (20th April 2017) - Raper, Daniel M S; Ding, Dale; Buell, Thomas J; Crowley, R Webster; Starke, Robert M; Liu, Kenneth C
Abstract: BACKGROUND: Elevated body mass index (BMI) has been correlated with worse outcomes after treatment for idiopathic intracranial hypertension (IIH). Venous sinus stenting (VSS) has emerged as a safe and effective treatment for a subset of patients with IIH and evidence of venous sinus stenosis. However, the association between BMI and the efficacy of VSS remains poorly characterized. OBJECTIVE: To determine, in a retrospective cohort study, the effect of BMI on preoperative mean intracranial venous pressure (MVP) and post-VSS outcomes. METHODS: We performed a retrospective evaluation of a prospectively collected database of patients with IIH and intracranial venous sinus stenosis who underwent VSS. Patient demographics and treatment factors, including pre- and postprocedural trans-stenosis pressure gradients, were analyzed to identify the relationship between BMI and outcomes after VSS. RESULTS: Increasing BMI was significantly correlated with higher maximum MVP ( P = .013) and higher trans-stenosis pressure gradient ( P = .043) prior to treatment. The degrees of improvement in maximum MVP and pressure gradient after VSS were greatest for obese and morbidly obese patients (BMI > 30 kg/m 2 ). Maximum poststent MVP, clinical outcomes, and stent-adjacent stenosis requiring retreatment after VSS were not significantly associated with BMI. CONCLUSION: We provide direct evidence for a positive correlation between BMI and intracranial venous pressure in patients with IIH. VSS affords a significantly greater amelioration of intracranial venous hypertension and stenosis for IIH patients with higher BMIs. As such, obesity should not be a deterrent for the use of VSS in the management of IIH.